Partisipasi Masyarakat dalam Program Bsps Melalui Upaya Keswadayaan Demi Mewujudkan Rumah Layak Huni di Desa Pucangombo - Aini, Dian Nur; Huda, Syamsul; Fitria, Anisa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted to determine community participation in the BSPS program through self-help efforts to create livable houses in Pucangombo Village. The research in this journal article applies a qualitative descriptive method because it is considered that it is easy to find information that can be accessed starting from time constraints, as well as the place to conduct research. Population growth tends to increase every year, conditions like this will result in various problems such as increasing housing needs, poverty rates, and slum areas. The Directorate General of the Ministry of Public Works and Public Housing as the organizer of government affairs issued a breakthrough program in the form of Self-Help Housing Stimulant Assistance which aims to improve decent housing that is healthy, safe, harmonious, orderly and sustainable for people with low incomes supported also by community participation through self-help forms . In this activity, community participation is categorized as enthusiastic, which can be seen from the optimal source of funds by looking at the form of self-help they have. So that the gains from the BSPS program are reducing inadequate housing and increasing the quality of community housing. Keywords: BSPS, Livable Houses, Nongovernmental